Stages of organising educational activities with migrant children in France - Yakymenko, V. (Journal of Education, Health and Sport, 2022)
The article identifies and characterizes the main stages of the organization of educational activities with migrant children in the French Republic during the period under study - the 70s of the twentieth century - the 20s of the twenty-first century. Given the changes in the regulatory and legal documentation (laws on education, directives, circulars of the Ministry of National Education of France, documents of international European organizations), which led to a revision of the purpose, tasks, content, principles, forms, and methods of organizing educational activities with migrant children in France, two stages of organizing this activity in the 70s of the twentieth century - 20s of the twenty-first century are scientifically substantiated: Stage I (70s - 90s of the twentieth century) - the stage of launching the development of issues of organizing educational activities with migrant children in France; Stage II (early 20s of the twenty-first century) - the stage of improving the organization of educational activities with migrant children in France. It has been found that the first stage (the 70s - 90s of the twentieth century) - the stage of launching the development of issues of organizing educational activities with migrant children in France - was characterized by the adoption of a number of legislative acts aimed at organizing educational activities with children from migrant families; defining the essence of the leading concepts; clearly defining the purpose and objectives of organizing this activity; formulating the leading principles of organizing educational activities with migrant children and the main directions of teachers' activities; outlining the principles of the It is proved that the second stage (the early 20s of the XXI century) - the stage of improving the organization of educational activities with migrant children in France - was characterized by further adoption of important legislative acts, expansion of the tasks of organizing this activity; enrichment of the content and activities of schools with migrant families; expansion of the principles of organization of the French education system; introduction of new forms of organization of educational activities; widespread use of project activities; organization of psychological support for migrant children. The article also describes the content, forms, and methods of teacher training for the organization of educational activities with migrant children during the study period.